2015
DOI: 10.1039/c5ra08412a
|View full text |Cite
|
Sign up to set email alerts
|

AhR-mediated activities and compounds in sediments of Meiliang Bay, Taihu Lake, China determined by in vitro bioassay and instrumental analysis

Abstract: Greater concentrations of TCDD-EQs and lesser concentrations of TEQs were found and a gradual decrease of AhR potency was confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…51 Xu and colleagues reported as high as 0.7−1.6, 2.7−6.9, and 11.1−22.9 pg/g dw TEQs of PCBs, PCDD/Fs, and PAHs, respectively. 52 Our previous study on PCB dechlorination in Taihu Lake sediment microcosms found that meta and para dechlorination occurred within 51 weeks under nitrate reducing conditions. 53 To better understand the potential of long-term PCB dechlorination, the PCB dechlorination rate, preference, and pathways were tracked in Taihu Lake sediment microcosms.…”
Section: ■ Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…51 Xu and colleagues reported as high as 0.7−1.6, 2.7−6.9, and 11.1−22.9 pg/g dw TEQs of PCBs, PCDD/Fs, and PAHs, respectively. 52 Our previous study on PCB dechlorination in Taihu Lake sediment microcosms found that meta and para dechlorination occurred within 51 weeks under nitrate reducing conditions. 53 To better understand the potential of long-term PCB dechlorination, the PCB dechlorination rate, preference, and pathways were tracked in Taihu Lake sediment microcosms.…”
Section: ■ Introductionmentioning
confidence: 95%
“…However, it has been suffering from various environmental issues. , Organochlorine pesticides (OCPs), polycyclic aromatic hydrocarbons (PAHs), PCBs, polychlorinated dibenzo- p -dioxins, and dibenzofurans (PCDD/Fs) were frequently detected in water, sediments, and aquatic products. However, most of the studies have focused on monitoring, source tracking, and ecological risk assessment. , The toxicity equivalents (TEQs) of PCDD/Fs in Taihu Lake sediments were higher than the threshold effect level of the sediment quality guidelines in Canada, ranging from 0.91 to 4.80 pg/g dw . Xu and colleagues reported as high as 0.7–1.6, 2.7–6.9, and 11.1–22.9 pg/g dw TEQs of PCBs, PCDD/Fs, and PAHs, respectively . Our previous study on PCB dechlorination in Taihu Lake sediment microcosms found that meta and para dechlorination occurred within 51 weeks under nitrate reducing conditions .…”
Section: Introductionmentioning
confidence: 99%
“…However, persistent organic pollutants newly added to the Stockholm Convention, such as polychlorinated naphthalenes, perfluorinated compounds, and hexabromocyclododecane, are currently rarely studied in the Caspian Sea at present. Persistent organic pollutants, including organochlorine pesticides, polychlorinated biphenyls, polychlorinated dibenzo-p-dioxins and dibenzofurans, polycyclic aromatic hydrocarbons, polybrominated diphenyl ethers, polychlorinated naphthalenes, hexabromocyclododecane, perfluorinated compounds, and tetrabromobisphenol A, are also present in different environmental compartments and biota in Chinese lake ecosystems (Qiu et al 2004;Zhang and Jiang 2005;Qiao et al 2006;Wang et al 2007Wang et al , 2016aWang et al , 2016bWen et al 2008;Yang et al 2011;Yu et al 2012;Zhang et al 2012;Zhou et al 2012aZhou et al , 2012bXu et al 2013Xu et al , 2015Cui 2018;Liu et al 2018;Wei et al 2019;Xiang et al 2019).…”
Section: Persistent Organic Pollutants In Lake and Ocean Ecosystemsmentioning
confidence: 99%
“…However, persistent organic pollutants newly added to the Stockholm Convention, such as polychlorinated naphthalenes, perfluorinated compounds, hexabromocyclododecane, etc., are rarely studied in the Caspian Sea at present. Persistent organic pollutants, including organochlorine pesticides, polychlorinated biphenyls, polychlorinated dibenzo-p-dioxins and dibenzofurans, polycyclic aromatic hydrocarbons, polybrominated diphenyl ethers, polychlorinated naphthalenes, hexabromocyclododecane, perfluorinated compounds and tetrabromobisphenol A, are also present in different environmental compartments and biota in Chinese lake ecosystems (Qiu et al 2004;Zhang and Jiang 2005;Qiao et al 2006;Wang et al 2007;Wen et al 2008;Yang et al 2011;Yu et al 2012;Zhang et al 2012;Zhou et al 2012a, b;Xu et al 2013Xu et al , 2015Wang et al 2016a, b;Cui 2018;Liu et al 2018;Wei et al 2019;Xiang et al 2019).…”
Section: Persistent Organic Pollutants In Lake and Ocean Ecosystemsmentioning
confidence: 99%